2011
DOI: 10.1111/j.1365-2958.2011.07827.x
|View full text |Cite
|
Sign up to set email alerts
|

Two oppositely oriented arrays of low-affinity recognition sites in oriC guide progressive binding of DnaA during Escherichia coli pre-RC assembly

Abstract: Summary The onset of chromosomal DNA replication requires highly precise and reproducible interactions between initiator proteins and replication origins to assemble a pre-replicative complex (pre-RC) that unwinds the DNA duplex. In bacteria, initiator protein DnaA, bound to specific high and low affinity recognition sites within the unique oriC locus, comprises the pre-RC, but how complex assembly is choreographed to ensure precise initiation timing during the cell cycle is not well understood. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
184
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(195 citation statements)
references
References 57 publications
(115 reference statements)
11
184
0
Order By: Relevance
“…We found that maintaining N pd = 5 was more difficult than the τ2l case. This result suggests that, for the left-half subcomplex, the complex is more stable with the same orientations of all five bindings, which is in agreement with the report by Rozgaja et al (15).…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…We found that maintaining N pd = 5 was more difficult than the τ2l case. This result suggests that, for the left-half subcomplex, the complex is more stable with the same orientations of all five bindings, which is in agreement with the report by Rozgaja et al (15).…”
Section: Resultssupporting
confidence: 83%
“…We demonstrated that the low-affinity site τ2 shares its binding orientation with other sites in the left-half subcomplex, which is in agreement with a recent DMS footprint assay (15). It is suggested in ref.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations